PET imaging of platelet derived growth factor receptor β in lung fibrosis - Olivia Wegrzyniak; Francesco Lechi; Johanna Rokka; Bogdan Mitran; Bo Zhang; Ulrika Thelander; John Löfblom; Fredrik Y. Frejd; Olle Korsgren; Gaetano Perchiazzi; Jonas Eriksson; Olof Eriksson (EJNMMI Radiopharmacy and Chemistry)
Abstract Background Lung diseases such as idiopathic pulmonary fibrosis and acute respiratory distress syndrome (ARDS) are associated with significant morbidity and mortality, with limited treatment options. Platelet-derived growth factor receptor beta (PDGFRβ) signaling pathway is a key driver of fibrogenesis in different organs. In the lungs, pericytes have a high PDGFRβ expression, and their role as immune regulators and progenitors of myofibroblasts is increasingly recognized. Non-invasive techniques to assess active lung tissue remodeling are needed to improve disease monitoring and treatment evaluation. This study aimed to evaluate [18F]TZ-Z09591, targeting PDGFRβ, for imaging pulmonary injuries in human biopsies, and in vivo in animal models of lung injury. Results [18F]TZ-Z09591 demonstrated high and specific binding to PDGFRβ-expressing cells. Autoradiography confirmed tracer uptake in lung injuries, including fibrotic foci, from human, rat, and pig lung tissues. In vivo positron emission tomography (PET) imaging of bleomycin-induced lung fibrosis in rats and an ARDS pig model showed significantly increased uptake in diseased lung segments compared to controls, especially in pulmonary injuries with collagen deposition, despite moderate background uptake. Conclusions This study demonstrated that [18F]TZ-Z09591 can assess PDGFRβ expression in pulmonary injuries, supporting its potential for non-invasive assessment of lung tissue remodeling. PET imaging targeting PDGFRβ could improve disease monitoring, and provide new insights into pulmonary fibrosis progression.